已知sin(π-x)-cos(π-x)=√2/3 (π/2(2)(sin(2π-x))^3+(cos(2π-x))的值

来源:学生作业帮助网 编辑:作业帮作业网 时间:2022/05/21 07:39:20
已知sin(π-x)-cos(π-x)=√2/3(π/2(2)(sin(2π-x))^3+(cos(2π-x))的值已知sin(π-x)-cos(π-x)=√2/3(π/2(2)(sin(2π-x))

已知sin(π-x)-cos(π-x)=√2/3 (π/2(2)(sin(2π-x))^3+(cos(2π-x))的值
已知sin(π-x)-cos(π-x)=√2/3 (π/2
(2)(sin(2π-x))^3+(cos(2π-x))的值

已知sin(π-x)-cos(π-x)=√2/3 (π/2(2)(sin(2π-x))^3+(cos(2π-x))的值
sin(π-x)-cos(π-x)=√2/3
sinx+cosx=√2/3(利用诱导公式,奇变偶不变,符号看限象)
(sinx+cosx)^2=(√2/3)^2=4/9=sinx^2+sinx^2+cosx^2+cosx^2
又sinx^2+cosx^2=1
所以2sinxcosx=-5/9
π/2